Antioxidant and Anti-Inflammatory Activity of Five Medicinal Mushrooms of the Genus Pleurotus - Stastny, Jan; Marsik, Petr; Tauchen, Jan; Bozik, Matej; Mascellani, Anna; Havlik, Jaroslav; Landa, Premysl; Jablonsky, Ivan; Treml, Jakub; Herczogova, Petra; Bleha, Roman; Synytsya, Andriy; et al. (Antioxidants (Basel, Switzerland), 2022)
Within the group of higher fungi, edible medicinal mushrooms have a long history of being used as food and in folk medicine. These species contain biologically active substances with many potential beneficial effects on human health. The Pleurotus genus is representative of medicinal mushrooms because Pleurotus ostreatus is one of the most commonly cultivated culinary mushrooms. In our study, we focused on lesser-known species in the genus Pleurotus and measured their antioxidant and anti-inflammatory activity. We prepared extracts of the mushrooms and analyzed them using HPLC-HRMS, GC-MS, and 1H-NMR. Significant differences in biological activities were found among the Pleurotus spp. extracts. A MeOH extract of P. flabellatus was the most active as a radical scavenger with the highest ORAC, while a chloroform extract had significant anti-inflammatory COX-2 activity. The 80% MeOH extract of P. flabellatus contained the highest amounts of ergosterol, ergothioneine, and mannitol. The 80% MeOH extract of P. ostreatus Florida was the most active in the NF-κB inhibition assay and had the highest content of β-glucans (43.3% by dry weight). Given the antioxidant and anti-inflammatory properties of P. flabellatus, the potential therapeutic usefulness of this species is worth evaluating through in-depth investigations and confirmation by clinical trials.
Keywords: inflammation; basidiomycetes; radical scavenging effect; immunomodulatory effect; bioactivity; pink oyster mushroom; oyster mushroom; secondary metabolites; cyclooxygenase-2; Indian oyster mushroom